Aqueous Solutions of Poly[2‐(N‐morpholino)ethyl methacrylate]: Learning about Macromolecular Aggregation Processes from a Peculiar Three‐Step Thermoresponsive Behavior. Issue 6 (20th December 2015) - Eggers, Steffen; Fischer, Birgit; Abetz, Volker
Abstract : Aqueous solutions of narrowly distributed poly[2‐( N ‐morpholino)ethyl methacrylate], a biocompatible multiple stimuli‐responsive polymer, show a peculiar three‐step aggregation behavior upon heating, an effect which has hitherto barely been reported for other polymers. The phenomenon is discussed in terms of mesoglobule formation (first step) as well as by an unusual distinct disruption of hydrophobic hydration (second step) and hydrogen bonding to the hydrophilic aggregate surface (third step). Macroscopic precipitation only takes place after the third step, a behavior which resembles the denaturation and limited aggregation of proteins. Furthermore, the influence of different anions along the Hofmeister series is investigated, identifying salting‐out (kosmotropic) and salting‐in (chaotropic) effects. As an experimental tool to monitor the thermally induced aggregate growth, dynamic light scattering is used. The reported findings might lead to a more detailed understanding of both aggregation behavior of (biological) macromolecules and mechanistic processes involved in thermoresponsivity and salt‐responsivity of water soluble polymers. Abstract : This work deals with the remarkable three‐step aggregation behavior of poly[2‐( N ‐morpholino)ethyl methacrylate] as a multiresponsive biocompatible polymer. Besides different components in polymer and aggregate hydration, the influence of different anions on the responsivity of the system is discussed. Conducted experiments can monitor the behavior of the polymer in switchable devices, e.g., in nanocarriers for therapeutic agents in vivo.